2018
DOI: 10.1007/s12532-018-0145-6
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of 2-level polytopes

Abstract: A (convex) polytope P is said to be 2-level if for every direction of hyperplanes which is facet-defining for P , the vertices of P can be covered with two hyperplanes of that direction. The study of these polytopes is motivated by questions in combinatorial optimization and communication complexity, among others. In this paper, we present the first algorithm for enumerating all combinatorial types of 2-level polytopes of a given dimension d, and provide complete experimental results for d 7. Our approach is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Moreover, if S is a slack matrix of polytopes P 1 , P 2 , then P 1 and P 2 are affinely isomorphic. For proofs of these facts and more properties of slack matrices, see, e.g., [8].…”
Section: Simplicial Glued Products Slack Matrices and K-productsmentioning
confidence: 99%
“…Moreover, if S is a slack matrix of polytopes P 1 , P 2 , then P 1 and P 2 are affinely isomorphic. For proofs of these facts and more properties of slack matrices, see, e.g., [8].…”
Section: Simplicial Glued Products Slack Matrices and K-productsmentioning
confidence: 99%
“…We consider possible generalizations of the conjecture based on the H−embedding of 2-level polytopes. Those are defined in [7], where it is shown that the family of 2-level polytopes of dimension d is affinely equivalent to the family of integral polytopes of the form…”
Section: Polytopes With Structured Linear Relaxationsmentioning
confidence: 99%
“…facets) of P , and d is its dimension. Whether this holds for all 2-level polytopes was asked in [7], and experimental results from [16] showed it true for d ≤ 7. The key to most of our proofs is a deeper understanding of the relations among those polytopes and their underlying combinatorial structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such polytopes play an important role in the theory of semidefinite representations of polyhedra and have been the focus of recent interest. Moreover, they comprise a very large family that includes many interesting polytopes; see for example [ACF18] for combinatorially relevant examples and [BFFFMP19] for a full enumeration in dimension up to 7.…”
Section: Introductionmentioning
confidence: 99%